(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the Turkic layer of the anthroponyms of the Uzbek language and its formation are subjected to scientific analysis. Based on the historical-comparative method, the historical formation of the original Turkic anthroponyms, their structural-semantic aspects, and the motivational features of naming a child in ancient Turkic tribes are analyzed with the help of examples. The article found that the original Turkic anthroponyms were derived mainly from appellatives and were formed based on the names of things, customs, and natural phenomena related to the daily life of the Turkic tribes.